Women's compliance with nutrition and lifestyle recommendations before pregnancy: General population cohort study - Inskip, H; Crozier, SR; Godfrey, K; Borland, SE; Cooper, C; Robinson, S (2009)
Objective: To examine the extent to which women planning a pregnancy comply with recommendations for nutrition and lifestyle. Design: Prospective cohort study. Setting: Southampton, United Kingdom. Participants: 12 445 non-pregnant women aged 20-34 recruited to the Southampton Women's Survey through general practices, 238 of whom became pregnant within three months of being interviewed. Main outcome measures: Folic acid supplement intake, alcohol consumption, smoking, diet, and physical activity before pregnancy. Results: The 238 women who became pregnant within three months of the interview were only marginally more likely to comply with recommendations for those planning a pregnancy than those who did not become pregnant in this period. Among those who became pregnant, 2.9% (95% confidence interval 1.2% to 6.0%) were taking 400 μg or more of folic acid supplements a day and drinking four or fewer units of alcohol a week, compared with 0.66% (0.52% to 0.82%) of those who did not become pregnant. 74% of those who became pregnant were nonsmokers compared with 69% of those who did not become pregnant (P=0.08). Women in both groups were equally likely to consume five or more portions of fruit and vegetables a day (53% in each group, P=1.0), but only 57% of those who became pregnant had taken any strenuous exercise in the past three months compared with 64% in those who did not become pregnant (P=0.03). Conclusion: Only a small proportion of women planning a pregnancy follow the recommendations for nutrition and lifestyle. Greater publicity for the recommendations is needed, but as many pregnancies are unplanned, improved nutritionand lifestyles of women of childbearing age is also required.